2018
DOI: 10.1007/s00264-018-4047-z
|View full text |Cite
|
Sign up to set email alerts
|

Differences in total blood loss and transfusion rate between different indications for shoulder arthroplasty

Abstract: The most important susceptible factor that affects the TBL is the surgery time. Transfusion rates are higher in patients with fracture arthroplasty than after primary arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…The higher rates of transfusion in fracture patients was previously thought to be in part a result of reduced surgical preparation time compared to patients undergoing elective primary SA. 18 Our findings dispute this claim since patients with both acute and chronic fractures had increased transfusion rates despite sufficient surgical preparation times in chronic fracture patients. More research must be conducted to identify what causes fracture patients to be at a higher risk for transfusion even after the initial insult has presumably healed.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…The higher rates of transfusion in fracture patients was previously thought to be in part a result of reduced surgical preparation time compared to patients undergoing elective primary SA. 18 Our findings dispute this claim since patients with both acute and chronic fractures had increased transfusion rates despite sufficient surgical preparation times in chronic fracture patients. More research must be conducted to identify what causes fracture patients to be at a higher risk for transfusion even after the initial insult has presumably healed.…”
Section: Discussioncontrasting
confidence: 56%
“…Clinical factors such as preoperative hemoglobin levels impact the risk for transfusion. [14][15][16]18 To our knowledge, this is the first study to investigate differences in transfusion rates and preoperative hemoglobin levels between multiple primary SA indications including OA, RCA, acute fracture ( 4 weeks old), chronic fracture ( > 4 weeks old), as well as for various revision indications including with and without active PJI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, XU et al identified that coronary heart disease is one of the risk factors for transfusion in patients following total joint arthroplasty [24]. In addition, Malcherczyk et al [25] reported that coronary heart disease is a risk factor for postoperative blood transfusion in patients with shoulder arthroplasty. However, the potential mechanism between coronary heart disease and transfusion remains unclear.…”
Section: Discussionmentioning
confidence: 99%